2005
DOI: 10.1037/0012-1649.41.1.135
|View full text |Cite
|
Sign up to set email alerts
|

Peer Influences on Risk Behavior: An Analysis of the Effects of a Close Friend.

Abstract: Cross-sectional research suggests that peer influence has a moderate to strong impact on adolescent risk behavior. Such estimates may be inflated owing to third-variable confounds representing either friendship selection effects or the operation of parallel events. Approximately 1,700 peer dyads in Grades 7 to 11 were studied over a 1-year period to estimate the influence of closest friends on sexual activity and binge drinking. Analyses suggested that peer influence was small but reliable when both selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
263
2
8

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(289 citation statements)
references
References 53 publications
10
263
2
8
Order By: Relevance
“…Children do not select into peer groups at random, but rather become friends with children who are like them (Guo, 2005;Jaccard, 2005). This means that aggressive children are more likely to become friends with other aggressive children.…”
Section: Delinquencymentioning
confidence: 99%
“…Children do not select into peer groups at random, but rather become friends with children who are like them (Guo, 2005;Jaccard, 2005). This means that aggressive children are more likely to become friends with other aggressive children.…”
Section: Delinquencymentioning
confidence: 99%
“…3 The aim of this paper is to go beyond the black box approach of peer effects in weight gain and try to identify one crucial mechanism through which peer effects in adolescence overweight may flow: eating habits (as 1 While Cohen-Cole and Fletcher (2008) found that there is no evidence of peer effects in weight gain, most of the literature is consistent with the presence of these effects. 2 Researchers also found that friends had a significant effect in adolescent smoking, drinking, illicit drug use (Clark and Loheac, 2007) and risky sex (Jaccard et al, 2005). 3 One recent exception is Yakusheva et al (2010) who look at peer effects in weight gain and in weight management behaviours such as eating and physical exercise, using randomly assigned pairs of roommates in freshman year.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, best friends are the main focus when studying peer influences (e.g., Andrews et al 2002;Jaccard et al 2005;Poelen et al 2007). The drinking behaviour of best friends may be a useful parameter in measuring peer influence, since best friends spend much time together (Jost et al 1985) and play an important role in the lives of young adults (Hartup 1996).…”
Section: Introductionmentioning
confidence: 99%